RF front end receiver for WiMAX application - Othman, Abdul Rani; Hamidon, Abdul Hamid; Wasli, Chairulsyah; Mustaffa, Mohd Firdaus; Ting J. T. H (2010)
This paper presents the design of a high gain, low noise direct conversion Radio frequency(RF) front-end receiver system. The Front end receiver is designed to operate at 5.8 GHz compliant with IEEE 802.16 WIiMAX standard. The system consists of a low noise amplifier (LNA), a radio frequency amplifier (RFA), a power divider and two band pass filters. The overall performance of the RF front-end receiver system produced a gain of 52.4 dB. A cascaded LNA designed for the system produced a high gain of 36.8 dB. The RFA contributed an extra gain 15.6dB. The overall noise figure achieved for the system is 3.7 dB. The return loss achieved is -25.5 dB for the RFA. The radio frequency bandwidth recorded for the system is above 1120 MHz. The measured power divider insertion loss is 2.80 dB. Using microstrip technology for designing the Chebyshev filter, the insertion loss is 3.00 dB and the channel bandwidth recorded is 107 MHz which can accommodate 4 sub channels IEEE WiMAX standard.